Perancangan Sistem Pembelajaran Online Dengan Pendekatan Metode Waterfall (Studi Kasus: SMK PGRI 109 Tangerang) - Asep Suryadi; Andi Romansyah (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Information technology is growing rapidly from year to year. In the field of education, learning processes based on information technology are no longer unavoidable. Online learning is a scheme called e-learning that has the effect of transforming traditional education into a digital system. In this study, the data collection method used was interviews, observation and documentation to obtain information or data related to the research focus. The design of this application system uses an approach with the waterfall method which consists of the requirements analysis, design, implementation, testing/verification, and maintenance stages, with a web-based programming language including HTML for display design, PHP for creating dynamic websites and SQL as a data storage container. . The results of this research are that this e-learning application can optimize students' understanding of learning, images, animation, audio and video and the teaching and learning process continues when students or teachers are unable to attend..